2008
DOI: 10.1016/j.febslet.2008.10.053
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 is required for TAK1 stability but not for its activation in the pro‐inflammatory signaling pathway

Abstract: The protein kinase transforming-growth-factor-bactivated kinase-1 (TAK1) is a key regulator in the pro-inflammatory signaling pathway and is activated by tumor necrosis factor-a, interleukin-1 (IL-1) and lipopolysaccharide (LPS). We describe the identification of TAK1 as a client protein of the 90 kDa heat-shock protein (Hsp90)/cell division cycle protein 37 (Cdc37) chaperones. However, Hsp90 is not required for the activation of TAK1 as short exposure to the Hsp90 inhibitor, 17-(allylamino)-17-demethoxygeldan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
(38 reference statements)
1
18
0
Order By: Relevance
“…Interestingly, our results indicate that a one-hour treatment with 17-AAG results in the complete insolubility of IRAK-1 while only a fraction of TAK1 is insoluble under these conditions. Our data showing partial insolubility of TAK1 is consistent with the work by Liu et al (26) that reported that Hsp90 binding to TAK1 is required for its folding and stability, but is released when TAK1 binds to TAB1. Thus, the soluble fraction of TAK1 likely represents a stable form of TAK1 that does not form a protein complex with Hsp90.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our results indicate that a one-hour treatment with 17-AAG results in the complete insolubility of IRAK-1 while only a fraction of TAK1 is insoluble under these conditions. Our data showing partial insolubility of TAK1 is consistent with the work by Liu et al (26) that reported that Hsp90 binding to TAK1 is required for its folding and stability, but is released when TAK1 binds to TAB1. Thus, the soluble fraction of TAK1 likely represents a stable form of TAK1 that does not form a protein complex with Hsp90.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that the expression of TAK1 was decreased along with the increase of HSP70 and vise versa (Figure 2). It has been previously reported that HSP90 regulates IL-1β-induced signaling by interacting with TAK1 [26] and HSP90 is required for the folding and stability of TAK1 [30]. We thus further determined the impact of inducible HSP70 on the complex of HSP90-TAK1 in HeLa cells.…”
Section: Resultsmentioning
confidence: 92%
“…MKK4 is a direct substrate of TAK1, thus it is possible TAK1 also associates with Filamin A to stimulate MKK4/JNK signaling. Additionally, TAK1 is known to be a client of HSP90 (43). TAK1-mediated phosphorylation of a close relative, endoplasmin (HSP90B1), suggests TAK1 is capable of interacting with additional heatshock proteins.…”
Section: Discussionmentioning
confidence: 99%